1996
DOI: 10.1164/ajrccm.154.1.8680679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computed density and microscopic morphometry in pulmonary emphysema.

Abstract: The purpose of this prospective study was to verify whether the percentage area of lung occupied by lowest attenuation values on high-resolution computed tomography (HRCT) scans reflects microscopic emphysema and to compare this quantification with the information yielded by the most widely used pulmonary function tests (PFT). Preoperative HRCT scans were obtained with 1-cm intervals in 38 subjects. With a semiautomatic evaluation procedure, the percentage areas occupied by attenuation values inferior to thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
431
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 498 publications
(455 citation statements)
references
References 12 publications
13
431
2
9
Order By: Relevance
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The method has been recommended for use in longitudinal studies of emphysema and is currently considered to be better than functional tests for disease assessment. (6,16) In addition, previous studies have reported that the correlation between CT densitometry and macroscopic morphometry is higher than is that between macroscopic morphometry and subjective visual grading of emphysema.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The method has been recommended for use in longitudinal studies of emphysema and is currently considered to be better than functional tests for disease assessment. (6,16) In addition, previous studies have reported that the correlation between CT densitometry and macroscopic morphometry is higher than is that between macroscopic morphometry and subjective visual grading of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…In order to select a reference value for comparing the EI values in a given patient, we should take into consideration the radiation dose, (18,19) the slice thickness, (18) the reconstruction algorithm, (20) the type of scanner, (21) the HU range selected for lung segmentation (usually −1,024 HU to −400 HU or −1,024 HU to −250 HU), (19,22) and the HU threshold selected in order to distinguish between normal and emphysematous lung (usually −970 HU, −950 HU, or −910 HU). (11)(12)(13)22) Various HU thresholds have been proposed in order to distinguish between normal and abnormal lungs. (10)(11)(12)(13) The initial suggestion was a threshold of −910 HU for axial scanners, with thicker collimation (i.e., 10 mm), and for examinations performed with the administration of intravenous contrast medium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations